Effects of ultra-oxidized graphene oxide on the hydration of cement - Sheikh, Taimur Mazhar (2022)
While the use of concrete is widespread in the construction industry, cement’s poor flexural capacity and tendency to form cracks limit the potential strength development of concrete structures. Of late, concrete nanoreinforcement has gained attention, as it mitigates crack formation at the nanoscale, allowing for construction of more durable and stronger structures. Graphene oxide (GO) is a highly promising nanoreinforcement candidate due to its ease of dispersion in water, and subsequently the concrete mix. However, recent research has suggested that GO cement reinforcement is not only physical but chemical, as the hydrophilic GO provides water seeding points for cement hydration, leading to a denser microstructure which increases the flexural capacity of concrete. This research investigates the chemical interactions of GO and water, with the premise that if GO is synthesized with varying functional groups, its ability to seed water to cement will be altered. If the GO reinforcement to cement is chemical, then the physical properties of concrete with the different GO functional groups will be significantly altered. As such, four variants of GO were synthesized with varying chemical properties, but similar physical properties such as sheet sizes and thicknesses. The chemical difference between all GOs were confirmed via analytical characterization tests. Incorporation of these GOs in cement, mortar, and concrete confirmed significant impacts on strength, workability, and durability. Ultra-oxidized GOs, i.e. GOs with high presence of hydroxyl and epoxide groups showed >50% concrete mix workability, 30% increase in 28-day compressive strength, > 50% increase in 28-day flexural strength and a 42% reduction in 24 hour pore size development with respect to control concrete. Furthermore, different superplasticizer treatments to ultra-oxidized GO concretes showed consistently improved performance as well. Conversely, low hydroxyl GOs showed inconsistent results, with reduced workability and lower 28-day compressive strength of concrete with respect to control. The results confirm that GO nanoreinforcement is primarily a chemical interaction with concrete, incumbent on the presence of hydroxyl groups on the GO sheets. This research presents high potential for future implementation with physical reinforcement such as fibers or rebars. However, greater research must be undertaken to ensure GO nanoreinforcement does not impact or is not impacted by chemical admixtures in concrete.